The Subjective Comfort Test of Autism Hug Machine Portable Seat - Maula, Mohamad Izzur; Aji, Akhmad Lutfiyan; Aliyafi, M. Bahtiar; Afif, Ilham Yustar; Ammarullah, Muhammad Imam; Winarni, Tri Indah; Jamari, J. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This preliminary study proposes to investigate (i) the mean comfortable deep pressure of Autism Hug Machine Portable Seat (AHMPS) manual pull and inflatable wrap models; and (ii) the effect of using AHMPS in reducing anxiety in children with autism spectrum disorder (ASD). The first phase was done to determine the comfort test. Fifteen healthy adolescents (13 men and 2 women; aged 19-25 years) individuals volunteered to participate in the comfort test in determining the pressure of AHMPS, both manual pull, and inflatable wrap. The second phase was completed in children with ASD, in which the comforting pressure from the first phase was then applied to five children with ASD (4 boys and 1 girl; aged 8-15 years) from the Putra Mandiri Public Special School Semarang. All children were administered both the AHMPS inflatable wrap and manual pull as a deep pressure apparatus while traveling by bus. A pulse oximeter was used to measure heart rate variability (physiological arousal). The mean comfort pressure was obtained from 15 healthy subjects, which was 0.81 psi on the chest and 0.80 psi on the thigh for the manual pull; and 0.65 psi on the chest and 0.45 psi on the thigh for the inflatable wrap. In the second phase, the AHMPS manual pull did not significantly decrease heart rate with p=0.114, but the AHMPS inflatable wrap significantly decreased heart rate with a significance value of p=0.037. We conclude, therefore, the AHMPS inflatable wrap decreases physiological arousal in children with ASD.